Simultaneous in situ determination of U‐Pb and Sm‐Nd isotopes in monazite by laser ablation ICP‐MS - Dylan J. Goudie; Christopher M. Fisher; John M. Hanchar; James L. Crowley; John C. Ayers (Geochemistry, Geophysics, Geosystems)
Abstract Results are presented for in situ simultaneous determination of U‐Pb and Sm‐Nd isotopes in monazite using the Laser Ablation Split‐Stream (LASS) method. This method uses a laser ablation system coupled to a magnetic‐sector inductively coupled plasma mass spectrometer (HR) (ICP‐MS) for measuring U‐Pb isotopes and a multicollector (MC) ICP‐MS for measuring Sm‐Nd isotopes. Ablated material is split using a Y‐connector and transported simultaneously to both mass spectrometers. In addition to Sm and Nd isotopes, the MC‐ICP‐MS is configured to also acquire Ce, Nd, Sm, Eu, and Gd elemental abundances. This approach provides age, tracer isotope, and trace element data in the same ablation volume, reducing sampling problems associated with fine‐scale zoning in accessory minerals and minimizing the material needed for ablation. Precision and accuracy of the U‐Pb method (and the precision of the Sm‐Nd method) is demonstrated with results from well‐characterized monazite reference materials. The LASS results agree within uncertainty with the isotope dilution thermal ionization mass spectrometry (ID‐TIMS) U‐Pb dates. The accuracy of the Sm‐Nd method is assessed by comparing the LA‐MC‐ICP‐MS results with ID‐TIMS determinations on a well‐characterized, in‐house monazite reference material. The LASS method is then applied to monazite from the Birch Creek Pluton in the White Mountains of California as a case study to illustrate the utility of this method for solving geologic problems. The U‐Pb ages and Sm‐Nd isotopic data from the LASS method support the conclusions drawn from previous results that monazite can record timing and information about the source region(s) of hydrothermal fluids.